PERANAN KREATIVITAS DALAM BELAJAR - Sefrinal, Sefrinal; Neviyarni, Neviyarni; Afdal, Afdal; Handayani, Revi (STKIP Pesisir Selatan, 2025)
At present, students are not only required to master basic knowledge but also to develop creative thinking skills to face complex global challenges. Creativity in learning is defined as the ability to generate original, useful, and contextually relevant ideas. This study aims to describe the concept of creativity in learning, analyze its role in enhancing motivation and learning outcomes, identify the factors influencing creativity development, and formulate strategies that can be applied by teachers, schools, and external environments. The research method used is a library research approach with content analysis, focusing on primary and secondary literature related to creativity, learning, and development strategies. The findings indicate that creativity plays a significant role in fostering intrinsic motivation, deepening conceptual understanding, and improving academic achievement. Internal factors (cognitive ability, personality, motivation), external factors (classroom climate, teacher-student interaction), and contextual factors (culture, technology) influence students’ creativity development. In conclusion, fostering creativity is essential to improving the quality of education, requiring collaboration among schools, teachers, families, and communities to create an innovative and adaptive learning ecosystem.